Character Development Through Democracy-Based Islamic Education in the Family According to Hasan Langgulung - Annisa Regina Anandari; Supriyanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Character or behavior is the identity of every individual. And character is also a key to assessing the quality of an individual. If you want to be seen as good by someone, then your character or behavior must also be good, and vice versa, if someone's behavior or character is bad, then the judgment of others towards that person will also be bad. This character is not something trivial; character is a very sensitive matter and requires consistency in its development. It needs to be prepared to handle or face upcoming problems. Especially in this modern era, everything is advancing, especially in the field of information technology, where everything is easily accessible. In this year, there is a rampant news of moral degradation among teenagers in Indonesia. Yet, the key to the success of a nation lies in the next generation. If the successors experience moral degradation, the progress of Indonesia will automatically be hindered. Therefore, there needs to be a movement to improve the generation that has experienced moral degradation and prevention for the coming generation. One of the steps that can be taken is the development of character and the instillation of Islamic education to the young generation of Indonesia. For the instillation of education, it is closely related to schools as formal educational institutions. However, surprisingly, the instillation and development of Islam are considered more effective when instilled at home and in the living environment. In this essay, we will explore the discussion of Islamic education in the family from the perspective of Hasan Langgulung's thoughts. This research is a qualitative study. It falls under library research with a qualitative descriptive approach. The data analysis methods employed in this study include descriptive analysis, content analysis, and interpretative analysis.